Fretting wear coating material, preparation method thereof and fretting wear coating

By applying a micro-wear coating material composed of MCrAlYX and spherical hexagonal boron nitride on the surface of the titanium alloy blade tenon, the problem of micro-wear wear of titanium alloy blade tenon in the prior art is solved, and its micro-resistant resistance is significantly improved Dynamic wear performance and service life.

CN119392075APending Publication Date: 2025-02-07AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411551802.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively protect the micro-moving wear of titanium alloy blade tenons above 550°C, resulting in a greatly reduced fatigue life of aircraft engine blade tenons.

Method used

A micro-weather coating material, including 85 to 95 parts of MCrAlYX as the bonding phase, was used, and 5 to 15 parts of spherical hexagonal boron nitride, the latter including a nickel layer, as the lubricating phase. This material forms a coating on the surface of the titanium alloy blade tenon through plasma spraying process, which significantly improves its anti-micro wear performance.

Benefits of technology

The coating material significantly reduces the micro-wear rate above 550°C, improves the anti-micro-wear performance, extends the service life of the titanium alloy blade tenon, and enhances its reliability under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115289610000111
    Figure BDA0005115289610000111
  • Figure HDA0005115289620000011
    Figure HDA0005115289620000011
  • Figure HDA0005115289620000012
    Figure HDA0005115289620000012
Patent Text Reader

Abstract

The invention discloses a fretting wear coating material which comprises the following components in parts by weight: 85-95 parts of MCrAlYX and 5-15 parts of spherical hexagonal boron nitride, and the spherical hexagonal boron nitride comprises a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the hexagonal boron nitride body; in the MCrAlYX, M is selected from Ni and / or Co, and X is selected from Ta and / or Si. The invention further discloses a preparation method of the composite material and a fretting wear coating. The MCrAlYX is used as a binding phase, and the spherical hexagonal boron nitride comprising the spherical hexagonal boron nitride body and the nickel layer formed on the surface of the hexagonal boron nitride body is used as a lubricating phase, so that the fretting wear resistance of the coating, especially the fretting wear resistance at the temperature of 550 DEG C or above, can be greatly improved. Experimental results show that compared with titanium-aluminum alloy, the wear rate of the coating provided by the invention is reduced by more than 10 times, and the fretting wear resisting effect is improved by more than 10 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal surface treatment, and in particular to a fretting coating material and a preparation method thereof, and a fretting coating. Background Art

[0002] Fretting may cause friction and wear on the contact surface, causing component seizure, loosening, and power loss. It will also accelerate the initiation and expansion of fatigue cracks, greatly reducing the fatigue life of components. It is reported that fretting can reduce the fatigue life of components by 20% to 50%, so fretting damage is also called the cancer of industry. In aircraft engines, blades and impellers are often connected by tenon structures. The tenon / tenon groove connection is affected by centrifugal force and strong aerodynamic loads. There is normal pressure on the contact surface, and small amplitude relative sliding occurs at the same time. Therefore, multi-factor coupling damage such as centrifugal load-extrusion stress-vibration stress-micro-vibration wear will occur, which is easy to cause the gap between the blade tenon and the tenon groove to increase, vibration to increase, and stress concentration to induce the root fracture of the blade, thus constituting the hidden danger of fretting fatigue failure of the tenon of the aircraft engine blade. Fretting damage of titanium alloy components is particularly serious in the aerospace industry. It is estimated that the proportion of design fretting damage in aircraft structural damage is as high as 90%. It can be seen that fretting wear has become the main cause of engine tenon failure and will also affect the overall life and reliability of the engine.

[0003] Preparation of anti-fretting wear coating on the surface of components is an effective means to improve their resistance to fretting wear and fatigue. The fretting wear and fatigue coating of the blade tenon of the current aircraft engine compressor is mainly prepared by plasma spraying process, such as CuNiIn, to improve the fretting fatigue damage of titanium alloy blades. The coating performance is greatly improved compared with the early metal and dry film lubricating coatings. However, the long-term service temperature of CuNiIn can only reach 315℃, which is difficult to meet the use requirements of the titanium aluminum alloy blade tenon of the new engine compressor at more than 550℃.

[0004] Therefore, how to improve the anti-fretting wear performance of titanium alloy blades above 550°C and increase the service life and reliability of titanium alloy materials remains an important issue that needs to be solved in this field. Summary of the invention

[0005] In view of this, the present application provides a fretting coating material and a preparation method thereof, wherein the fretting coating material has fretting protection stability above 550°C, reduces the fretting wear of the engine blade tenon, and has certain anti-oxidation properties.

[0006] The present application provides a fretting coating material, which comprises, by weight, 85 to 95 parts of MCrAlYX and 5 to 15 parts of spherical hexagonal boron nitride, wherein the spherical hexagonal boron nitride comprises a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the hexagonal boron nitride body;

[0007] In the MCrAlYX, M is selected from Ni and / or Co, and X is selected from Ta and / or Si.

[0008] The micro-wear coating material provided in the present application includes MCrAlYX, which, as a bonding phase, has high temperature resistance and oxidation resistance, and can significantly improve the use temperature and friction reduction and wear resistance of the coating material system. In the MCrAlYX component, M can be Ni or Co alone, or a combination of Ni and Co, preferably Ni; X can be an active element, such as Ta, Si, preferably Ta. In some specific implementations, the MCrAlYX components are NiCoCrAlYTa, CoCrAlYSi, NiCrAlYSi, etc. In some specific implementations, the weight of the MCrAlYX is 85 to 95 parts. In some specific implementations, the particle size of the MCrAlYX is 5μm to 38μm. The present application has no special restrictions on the source of MCrAlYX, and it can be purchased directly on the market. Since NiCoCrAlYTa has excellent oxidation resistance and stability below 1100°C, and hexagonal boron nitride (hBN) is relatively stable at 850°C, the designed material system can also be used for micro-motion protection of turbine blade tenons at higher temperatures and more stringent service conditions. It can also be expanded to high-temperature micro-motion wear protection above 550°C for key components in gas turbines, nuclear industry, aerospace, etc.

[0009] The fretting coating material provided by the present application includes spherical hexagonal boron nitride with nickel plating on the surface, which, as a lubricating phase, has good compatibility with the bonding phase MCrAlYX, and makes the obtained fretting coating material have good fluidity, can smoothly deliver powder, and improve the deposition efficiency of the powder. The spherical hexagonal boron nitride includes a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the hexagonal boron nitride body. In some specific implementations, the median particle size of the spherical hexagonal boron nitride body is 30μm to 80μm, which can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, preferably 50μm to 80μm, and more preferably 50μm to 60μm. By controlling the particle size of the spherical hexagonal boron nitride body, the mixing with the MCrAlYX component is promoted to be uniform, and the lamellar structure of the spherical hexagonal boron nitride will not be destroyed. The lubricating phase can be evenly distributed in the coating, which has a good lubrication and wear reduction effect. In some specific implementations, the thickness of the nickel layer is 0.1 μm to 0.5 μm, which can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, preferably 0.1 μm to 0.3 μm. By controlling the thickness of the nickel-plated layer of spherical hexagonal boron nitride, its compatibility with MCrAlYX can be increased, and the mixing is more uniform. In some specific implementations, the spherical hexagonal boron nitride body is formed by mixing lamellar hexagonal boron nitride, water and a binder, granulating and then sintering, wherein the length of the lamellar hexagonal boron nitride is 10 μm to 30 μm, preferably 15 μm to 25 μm; the thickness is 0.5 μm to 1 μm. In some specific implementations, the nickel layer coverage of the spherical hexagonal boron nitride is 70% to 100%, preferably 80% to 95%. In some specific implementations, the weight proportion of spherical hexagonal boron nitride in the fretting coating material is 5 to 15 parts.

[0010] In the present application, the spherical hexagonal boron nitride can be prepared according to the following method:

[0011] The nitrogen source, the boron source and the salt medium are mixed and reacted to obtain lamellar hexagonal boron nitride;

[0012] The lamellar hexagonal boron nitride, water and a binder are mixed, granulated and then sintered to obtain a spherical hexagonal boron nitride body;

[0013] A nickel layer is formed on the surface of the spherical hexagonal boron nitride body to obtain nickel-plated spherical hexagonal boron nitride.

[0014] The present application first reacts with nitrogen source, boron source and salt medium as raw materials, and obtains lamellar hexagonal boron nitride. In some specific implementations, the nitrogen source includes but is not limited to urea, melamine, etc., preferably urea; the boron source includes but is not limited to borax, boric acid, etc., preferably borax; the salt medium includes but is not limited to sodium chloride, potassium chloride, etc., preferably a mixture of sodium chloride and potassium chloride, and the mass ratio of sodium chloride to potassium chloride is preferably 3:7 to 6:4. In some specific implementations, the nitrogen source and the boron source are first mixed to form substance A, and then substance A is mixed with the salt medium and ball milled to obtain a mixed substance, and the mixed substance is heat treated. After the reaction is completed, the reaction system is cooled to room temperature, and the obtained reaction product is washed, filtered, and dried to obtain lamellar hexagonal boron nitride. In some specific implementations, the molar ratio of the nitrogen source to the boron source is 2:1 to 4:1, and the ratio of the total molar number of the salt medium to the boron source and the nitrogen source is 2:1 to 4:1. In some specific implementations, the ball milling time is 8h to 24h, and the ball milling speed is 150rpm to 200rpm. In some specific implementations, the temperature of the heat treatment is 1100℃ to 1300℃, the time of the heat treatment is 3h to 5h, and the heating rate of the heat treatment is 5℃ / min to 10℃ / min. In some specific implementations, the obtained product is washed with a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 2wt.% to 4wt.%. In some specific implementations, the temperature of drying after washing is 80℃ to 120℃, and the time is 8h to 24h. In some specific implementations, the thickness of the lamellar hexagonal boron nitride is 0.5μm to 1μm.

[0015] After the obtained lamellar hexagonal boron nitride is mixed with deionized water, a binder, a dispersant and a sintering aid and stirred to obtain a slurry, and the slurry is spray granulated and sintered to obtain a spherical hexagonal boron nitride body. In some specific implementations, the binder is polyvinyl alcohol. In some specific implementations, in the slurry, the binder mass percentage is 0.5% to 1%, the slurry solid content is 48% to 53%, the dispersant mass percentage is 1% to 1.5%, and the sintering aid mass percentage is 0.3% to 0.8%. In some specific implementations, during the stirring process, the ball-to-material ratio is 3:1 to 5:1, the stirring speed is 40r / min to 80r / min, the stirring time is 1h to 2h, and the slurry pH value is 6.5 to 7.5. In some specific implementations, the inlet temperature of the spray granulation is 210°C to 230°C, the outlet temperature is 100°C to 110°C, the cavity air temperature is 140°C to 180°C, and the atomizing air flow rate is 11m 3 / h to 15m 3 / h, the speed of the centrifugal atomizer is 10000r / min to 12000r / min, and the feed rate is 40rpm to 60rpm. In some specific implementations, the sintering temperature is 900℃ to 1000℃, and the sintering time is 3h to 5h. After sintering, the obtained product is sieved to obtain a spherical hexagonal boron nitride body of the required particle size. In some specific implementations, the particle size of the spherical hexagonal boron nitride body is 30μm to 80μm. Spherical hexagonal boron nitride is prepared by a molten salt method and a spray granulation process. On the basis of ensuring the high-temperature lubrication performance of spherical hexagonal boron nitride, it effectively alleviates the problem that small-particle spherical hexagonal boron nitride is easily blown away by airflow during spraying, has poor fluidity, and cannot be smoothly fed powder, thereby improving the deposition efficiency of the powder.

[0016] After obtaining the spherical hexagonal boron nitride body, a nickel layer is formed on its surface to obtain the spherical hexagonal boron nitride. In some specific implementations, the present application adopts the following method to form the nickel layer:

[0017] The spherical hexagonal boron nitride body is subjected to sensitization treatment, activation treatment and chemical nickel plating to obtain the spherical hexagonal boron nitride.

[0018] In some specific implementations, the sensitizing solution for the sensitization treatment includes: SnCl2·H2O and hydrochloric acid with a concentration of 10g / L to 20g / L, preferably 12g / L to 18g / L. This application does not have any special restrictions on the time of the sensitization treatment, and those skilled in the art can choose according to their needs. In some specific implementations, the activation solution for the activation treatment includes: PbCl2 and hydrochloric acid with a concentration of 0.3g / L to 0.8g / L, preferably 0.4g / L to 0.6g / L. After activation, it is washed and then nickel-plated. In some specific implementations, the chemical plating solution for chemical nickel plating includes: 10g / L to 15g / L nickel sulfate, 5g / L to 10g / L hypophosphite and 1g / L to 3g / L sodium citrate. It can be understood by those skilled in the art that the solvent of the chemical plating solution is water. In some specific implementations, the pH value of the chemical plating solution is 8 to 9. In some specific implementations, the loading amount of the spherical hexagonal boron nitride body is 10g / L to 25g / L, preferably 15g / L to 20g / L; the chemical nickel plating is preferably heated in a water bath, and the heating temperature is 60°C to 90°C, preferably 70°C to 80°C. In some specific implementations, the chemical nickel plating is preferably carried out under stirring, and the stirring speed is 100r / min to 150r / min. In some specific implementations, the nickel plating is stopped when the coverage of the spherical hexagonal boron nitride is more than 70%.

[0019] The present application adopts a molten salt method to prepare lamellar hexagonal boron nitride, and controls the length, thickness and crystallinity of the lamellar hexagonal boron nitride by controlling key parameters such as the reactant ratio, heating rate and holding time; then a spray granulation process is adopted to prepare spherical hexagonal boron nitride, and the sphericity and density of the spherical hexagonal boron nitride body are controlled by controlling key parameters such as slurry viscosity, turntable speed and inlet and outlet temperatures. Secondly, a layer of nickel is plated on the surface of the spherical hexagonal boron nitride body, and the thickness and coverage of the nickel layer are controlled by controlling key parameters such as the loading amount of hBN and the stirring speed. The obtained spherical hexagonal boron nitride has good fluidity after being mixed with MCrAlYX alloy powder, which is suitable for spraying process, and the prepared coating has excellent anti-fretting wear effect at 550°C. The preparation method has the advantages of simple operation and fast preparation speed, and can alleviate the failure problem of high-temperature fretting wear parts above 550°C in the fields of aviation, aerospace, and mechanical equipment, and improve the service life and reliability of parts.

[0020] The present application also provides a method for preparing a fretting wear coating material, comprising:

[0021] Spherical hexagonal boron nitride is mixed with MCrAlYX to obtain a fretting wear coating material; the spherical hexagonal boron nitride comprises a spherical hexagonal boron nitride body and a nickel layer formed on the surface thereof.

[0022] Spherical hexagonal boron nitride and MCrAlYX are described above, and the present application will not repeat them here. In some specific implementations, the mixing is performed in a pot mill, the mixing speed is 60 r / min to 80 r / min, and the mixing time is 1 h to 3 h.

[0023] The present application also provides a fretting coating, which is formed on the surface of an alloy substrate by the fretting coating material. The present application has no special restrictions on the method for forming the fretting coating, and any commonly used method known to those skilled in the art can be used, such as atmospheric plasma spraying. The present application has no special restrictions on the alloy substrate, which can be a TiAl alloy or the like.

[0024] The micro-motion wear material provided in this application can be used for aircraft engine blades, and can also be used for micro-motion protection of turbine blade tenons at higher temperatures and more stringent service conditions. It can also be expanded to high-temperature micro-motion wear protection above 550°C for key components in gas turbines, nuclear industry, aerospace, etc.

[0025] The fretting wear coating material provided by the present application comprises 85 to 95 parts of MCrAlYX and 5 to 15 parts of spherical hexagonal boron nitride by weight, wherein the spherical hexagonal boron nitride comprises a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the hexagonal boron nitride body; in the MCrAlYX, M is selected from Ni and / or Co, and X is selected from Ta and / or Si. The present application uses MCrAlYX as a bonding phase and spherical hexagonal boron nitride comprising a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the hexagonal boron nitride body as a lubricating phase, which can greatly improve the anti-fretting wear performance of the coating, especially the anti-fretting wear performance above 550°C. Experimental results show that compared with titanium aluminum alloy, the wear rate of the coating provided by the present application is reduced by more than 10 times, and the anti-fretting wear effect is improved by more than 10 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of spherical hexagonal boron nitride in Example 1 of the present application;

[0027] Figure 2 This is a surface morphology of the fretting coating material in Example 1 of the present application;

[0028] Figure 3 This is a cross-sectional morphology of the fretting wear coating in Example 1 of the present application;

[0029] Figure 4 This is a scanning electron microscope image of spherical hexagonal boron nitride in Example 2 of the present application;

[0030] Figure 5 This is a surface morphology diagram of the fretting coating material in Example 2 of the present application;

[0031] Figure 6 This is a cross-sectional morphology of the fretting wear coating in Example 2 of the present application;

[0032] Figure 7 This is a comparison chart of the alloy friction coefficient between the fretting wear coating prepared in Example 2 of the present application and the TiAl alloy;

[0033] Figure 8 This is a comparison chart of the wear rates of the fretting coating prepared in Example 2 of the present application and the TiAl alloy. DETAILED DESCRIPTION

[0034] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0035] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0036] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0037] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0038] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0039] The present invention is further described below in conjunction with the following examples. The protection scope of the present invention is not limited by the following examples.

[0040] Comparative Example 1

[0041] 1. Using borax as a boron source and urea as a nitrogen source, urea and borax are mixed in a molar ratio of 2:1 as a reaction material A;

[0042] 2. Use NaCl and KCl as salt medium and mix them in a mass ratio of 50:50 to form salt medium B.

[0043] 3. The salt medium B and the reaction material A at a molar ratio of 2:1 were ball-milled for 12 hours to obtain a mixed material C at a ball milling speed of 150 rpm.

[0044] 4. Place the mixed substance C in a high-temperature furnace, pass nitrogen as the reaction protection gas, increase the temperature to 1300°C at a heating rate of 5°C / min, keep the temperature for 3 hours, and then cool down to room temperature along with the furnace.

[0045] 5. The product of step 4 was washed and filtered with a hydrochloric acid solution having a concentration of 2 wt.%, and then washed three times with deionized water. After drying at 80° C. for 18 h, lamellar hexagonal boron nitride with a thickness of 0.6 μm was obtained.

[0046] 6. The flaky hexagonal boron nitride in step 5 was mixed with NiCoCrAlYTa having a median particle size of 8 μm to 45 μm in a pot mill for 1 hour, wherein the mass percentage of the flaky hexagonal boron nitride was 10%, and the rotation speed was 60 r / min to obtain a fretting coating material.

[0047] The above-mentioned fretting coating material was tested with reference to the standard funnel method (Hall flowmeter) for determining the fluidity of metal powders in GB / T1482. The test results showed that the powder had no fluidity. The bonding strength of the coating plasma sprayed with the anti-fretting powder material prepared in Example 1 was 10.7 MPa.

[0048] Example 1

[0049] 1. Using borax as a boron source and urea as a nitrogen source, urea and borax are mixed in a molar ratio of 3:1 as a reaction material A;

[0050] 2. Use NaCl and KCl as salt medium and mix them into salt medium B in a mass ratio of NaCl to KCl of 40:60.

[0051] 3. Mix the salt medium B and the reaction material A at a molar ratio of 3:1 and ball mill for 12 hours to obtain a mixed material C. The ball milling speed is 180 rpm.

[0052] 4. Place the mixed substance C in a high-temperature furnace, pass nitrogen as the reaction protection gas, increase the temperature to 1200°C at a heating rate of 7°C / min, keep the temperature for 4 hours, and then cool down to room temperature along with the furnace.

[0053] 5. The product of step 4 was washed and filtered with a 3 wt.% hydrochloric acid solution, then washed four times with deionized water, and dried at 100°C for 10 hours to obtain lamellar hexagonal boron nitride with a thickness of 0.8 μm.

[0054] 6. The lamellar hexagonal boron nitride, deionized water, binder (PVA), dispersant and sintering aid are stirred in a certain proportion to form a slurry, the ball-to-material ratio is 4:1, the rotation speed is 60r / min, the time is 1.5h, and the slurry pH value is controlled at 7.0; the binder (PVA) content is 0.8wt.%, the slurry solid content is 50%, the dispersant content is 1.2wt.%, and the sintering aid content is 0.5%.

[0055] 7. Use a centrifugal spray dryer to spray granulate the slurry. The spray drying conditions are as follows: the inlet temperature of the hot air is 220°C, the outlet temperature is 105°C, the cavity air temperature is 150°C, and the atomizing air flow rate is 13m 3 / h, the speed of the centrifugal atomizer was 11000r / min, and the feed rate was 50rpm to obtain the powder after spray granulation.

[0056] 8. The spray granulated powder was sintered at 1000°C for 4 hours, and sieving was performed to obtain a spherical hexagonal boron nitride body with a median particle size D(50) of 80 μm.

[0057] 9. The spherical hexagonal boron nitride body obtained in step 8 is placed in a solution consisting of 15 g / L SnCl2·H2O and hydrochloric acid for sensitization treatment, and then the spherical hexagonal boron nitride body is placed in a mixed solution of 0.5 g / L PbCl2 and hydrochloric acid for activation treatment to obtain surface-activated spherical hexagonal boron nitride.

[0058] 10. Place the surface activated spherical hexagonal boron nitride in the prepared chemical nickel plating solution and replenishing solution, wherein the loading amount of hBN is between 15g / L, heat to 80°C in a water pot, stir for chemical nickel plating, and obtain spherical hexagonal boron nitride, the stirring speed is 120r / min, and the pH value of the reaction solution is 8.5. The chemical plating solution includes 10g / L nickel sulfate, 8g / L hypophosphite and 2g / L sodium citrate, the nickel plating thickness of the hBN surface is 0.3μm, and the coverage is 80%.

[0059] 11. The spherical hexagonal boron nitride in step 10 is mixed with NiCoCrAlYTa with a median particle size of 8 μm to 45 μm in a pot mill for 2 hours, wherein the mass percentage of the spherical hexagonal boron nitride is 10%, and the rotation speed is 70 r / min to obtain a fretting coating material.

[0060] The above-mentioned fretting coating material is tested according to the GB / T1482 metal powder fluidity determination standard funnel method (Hall flowmeter) and the test results show that the powder fluidity can reach 100s / 50g and the bulk density can reach 2.82g / cm 3 , with good spraying process performance, the coating is prepared on the surface of TiAl alloy by plasma spraying process, the deposition efficiency is improved by 10% compared with comparative example 1, and the bonding strength of the coating is 30MPa. The scanning electron microscope image of the spherical hexagonal boron nitride is as follows Figure 1 The surface morphology of the micro-wear coating material is shown in Figure 2 The cross-sectional morphology of the coating material of the micro-wear coating is shown in Figure 3 shown.

[0061] Example 2

[0062] 1. Using borax as a boron source and urea as a nitrogen source, urea and borax are mixed in a molar ratio of 4:1 as a reaction material A;

[0063] 2. Use NaCl and KCl as salt medium and mix them into salt medium B in a mass ratio of NaCl to KCl of 60:40.

[0064] 3. Mix the salt medium B and the reaction material A at a molar ratio of 4:1 and ball mill for 24 hours to obtain a mixed material C. The ball milling speed is 200 rpm.

[0065] 4. Place the mixed substance C in a high-temperature furnace, pass nitrogen as the reaction protective gas, the reaction temperature is 1300°C, the heating rate is 10°C / min, the insulation time is 5h, and then the temperature is cooled to room temperature along with the furnace.

[0066] 5. The product of step 4 was washed and filtered with a 4 wt.% hydrochloric acid solution, then washed five times with deionized water, and dried at 120° C. for 24 h to obtain lamellar hexagonal boron nitride with a thickness of 0.9 μm.

[0067] 6. The lamellar hexagonal boron nitride, deionized water, binder (PVA), dispersant and sintering aid are stirred in a certain proportion to form a slurry, the ball-to-material ratio is 4:1, the rotation speed is 80r / min, the time is 2h, and the slurry pH value is controlled at 7.5; the binder (PVA) content is 1wt.%, the slurry solid content is 53%, the dispersant content is 1.5wt.%, and the sintering aid content is 0.8wt.%.

[0068] 7. Use a centrifugal spray dryer to spray granulate the slurry. The spray drying conditions are as follows: the hot air inlet temperature is 230°C, the outlet temperature is 110°C, the cavity air temperature is 180°C, and the atomizing air flow rate is 15m 3 / h, the speed of the centrifugal atomizer was 12000r / min, and the feed rate was 60rpm to obtain the powder after spray granulation.

[0069] 8. The spray granulated powder was sintered at 1000°C for 5 hours, and sieving was performed to obtain a spherical hexagonal boron nitride body with a median particle size D(50) of 60 μm.

[0070] 9. The spherical hexagonal boron nitride body obtained in step 8 is placed in a solution consisting of 20 g / L SnCl2·H2O and hydrochloric acid for sensitization treatment, and then the spherical hexagonal boron nitride body is placed in a mixed solution of 0.8 g / L PbCl2 and hydrochloric acid for activation treatment to obtain surface-activated spherical hexagonal boron nitride.

[0071] 10. Place the surface activated spherical hexagonal boron nitride in the prepared chemical nickel plating solution and replenishing solution, wherein the loading amount of hBN is about 25g / L, heat to 90°C in a water pot, stir for chemical nickel plating, and obtain spherical hexagonal boron nitride, the stirring speed is 150r / min, and the pH value of the reaction solution is 9. The chemical plating solution is composed of 12g / L nickel sulfate, 8g / L hypophosphite and 1g / L sodium citrate, the nickel plating thickness on the hBN surface is 0.5μm, and the coverage is 85%.

[0072] 11. The spherical hexagonal boron nitride in step 10 and CoCrAlYSi with a median particle size of 8 μm to 45 μm are mixed in a pot mill for 3 hours, wherein the mass percentage of the spherical hexagonal boron nitride is 7%, and the rotation speed is 80 r / min to obtain a fretting coating material.

[0073] 12. The anti-fretting coating material in step 11 is used to prepare a coating on the surface of titanium aluminum alloy by plasma spraying process, and fretting wear tests are carried out at different temperatures. The friction and wear effects are shown in Table 1.

[0074] The scanning electron microscope image of the spherical hexagonal boron nitride is as follows Figure 4 The surface morphology of the micro-wear coating material is shown in Figure 5 The cross-sectional morphology of the coating material of the micro-wear coating is shown in Figure 6 The average friction coefficient of the fretting coating prepared by the fretting coating material at 650°C is 0.375 ( Figure 7 ), the fretting wear rate is 0.83×10 -6 mm 3 / Nm( Figure 8 ).

[0075] Table 1

[0076]

[0077] according to Figure 7 It can be seen that the anti-fretting friction coefficient of pure titanium aluminum alloy at 650°C is 0.6-0.8, and the comparative example 1 and examples 2-3 all play a role in reducing the friction coefficient compared with the pure titanium aluminum alloy. Compared with the flake hBN in comparative example 1, the spherical hBN with nickel plating on the surface in examples 1 and 2 can more significantly improve the fluidity and bulk density of the powder, enhance the bonding strength of the coating and reduce the friction coefficient of the coating under high temperature fretting wear.

[0078] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A fretting coating material, characterized in that: The composition comprises 85 to 95 parts of MCrAlYX and 5 to 15 parts of spherical hexagonal boron nitride in parts by weight, wherein the spherical hexagonal boron nitride comprises a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the hexagonal boron nitride body; In the MCrAlYX, M is selected from Ni and / or Co, and X is selected from Ta and / or Si.

2. The fretting coating material according to claim 1, characterized in that: The median particle size of the spherical hexagonal boron nitride body is 30 μm to 80 μm.

3. The fretting coating material according to claim 2, characterized in that: The spherical hexagonal boron nitride body is composed of lamellar hexagonal boron nitride.

4. The fretting coating material according to claim 3, characterized in that: The thickness of the lamellar hexagonal boron nitride is 0.5 μm to 1 μm, and the length of the lamellar hexagonal boron nitride is 10 μm to 30 μm.

5. The fretting coating material according to claim 1, characterized in that: The thickness of the nickel layer is 0.1 μm to 0.5 μm; The coverage rate of the nickel layer in the spherical hexagonal boron nitride is 70% to 100%.

6. A method for preparing a fretting coating material, characterized in that: include: Spherical hexagonal boron nitride is mixed with MCrAlYX to obtain a fretting wear coating material; The spherical hexagonal boron nitride comprises a spherical hexagonal boron nitride body and a nickel layer formed on the surface of the spherical hexagonal boron nitride body.

7. The preparation method according to claim 6, characterized in that: The spherical hexagonal boron nitride is prepared according to the following steps: The nitrogen source, the boron source and the salt medium are mixed and reacted to obtain lamellar hexagonal boron nitride; The lamellar hexagonal boron nitride, water and a binder are mixed, granulated and then sintered to obtain a spherical hexagonal boron nitride body; A nickel layer is formed on the surface of the spherical hexagonal boron nitride body to obtain the spherical hexagonal boron nitride.

8. The preparation method according to claim 7, characterized in that: The step of forming a nickel layer on the surface of the spherical hexagonal boron nitride body comprises: After the spherical hexagonal boron nitride body is subjected to sensitization treatment and activation treatment, chemical nickel plating is performed to form a nickel layer on the surface of the spherical hexagonal boron nitride body.

9. The preparation method according to claim 8, characterized in that: The sensitizing solution of the sensitization treatment includes: SnCl2·H2O and hydrochloric acid with a concentration of 10g / L to 20g / L, the activating solution of the activation treatment includes: PbCl2 and hydrochloric acid with a concentration of 0.3g / L to 0.8g / L; the plating solution of the chemical nickel plating includes: 10g / L to 15g / L nickel sulfate, 5g / L to 10g / L hypophosphite and 1g / L to 3g / L sodium citrate, and the coverage rate of the spherical hexagonal boron nitride is 70% to 100%.

10. A fretting coating, characterized in that: The fretting coating is formed by the fretting coating material according to any one of claims 1 to 5 or the fretting coating material prepared by the preparation method according to any one of claims 6 to 9.